Mental Wellbeing and Recreational Sports - Two Together for a Healthy Win - Implications for Higher Education Institutions - Aparna Pandey; Anjali Chopra; Shailaja Karve (ACHSM, 2023)
The current research highlights how recreational sports enhance student wellbeing and promote physical and mental health through positive social bonding. The Indian social fabric is culturally and traditionally more interconnected as Indians thrive on social networks and engage in several festivals, celebrations, and get-togethers across the year. Therefore, the pandemic and ensuing lockdown created a vacuum. The study explored how students at higher education institutes (HEIs) engaged in Recreational Sports during the lockdown and its role in increasing social bonds, experiencing a feeling of association, positive emotions, relaxing the mind, and promoting overall wellbeing. Further, the present study identifies factors that influence the intention to continue engaging in recreation sports on an ongoing basis (a behaviour that was picked up during the pandemic to cope with lockdown and isolation). The current need  is to understand how learning and developing behavioural competencies can be encouraged through active learning in open spaces to overcome social isolation as all types of physical-sports activities favor psychological wellbeing. The present study uses the TPB (Theory of Planned Behavior) framework to identify factors that influence the intention to continue engaging in recreation sports on an ongoing basis. Social contact time, with many shared experiences, has multiple benefits. It not only helps in stress release but also motivates and provides comfort in the company of friends and colleagues. Therein lies the importance and relevance of Outdoor Behavioral Experiential Learning (OBEL) and recreational sports.